Framework for the sustainable development of village tanks in cascades as an adaptation to climate change and for improved water security, Sri Lanka - K. T. N. Perera (IWA Publishing, 2021)
The 2030 Agenda for Sustainable Development, adopted by all UN member states, provides a policy framework for achieving sustainable development goals. The 13th SDG: Climate Action is fully dedicated to ‘taking urgent action to combat climate change and its impacts’. Increasing storage is a key adaptation strategy in the water sector, and restoration and rehabilitation of ancient village tanks have been identified as one of the Nationally Determined Contributions in Sri Lanka. Though the country has engaged in the restoration of village tanks for nearly 170 years, only around 50% of the ancient tanks amounting to around 16,000 are restored and in working condition. Hence, this study aims to identify a strategy for restoring the abandoned tanks in the country towards achieving Sustainable Development Goals. The study reviewed the evolution of policies and approaches adopted in developing village tanks and identified conceptual and technical drawbacks in the existing normative assessment approach. New conceptual and decision-making frameworks were developed, incorporating design-level strategic considerations identified while following a multidimensional and transdisciplinary approach. The approach presented would be a viable strategy to develop village tanks in cascades as sustainable social–ecological systems. Highlights Approaches used in developing village tanks for 170 years were reviewed.; Overlooking global development concepts in assessment affects tank restoration.; Sustainability and social–ecological aspects should be key determinants.; The proposed transdisciplinary approach guides developing village tanks sustainably.; Consistency of strategies and technical approaches with the policies are crucial for achieving goals and objectives.;